Get programming with Python in motion - Bell, Ana (Manning Publications, 2019)
"Don't know anything about programming? No problem! This video course is designed for people who have never written a line of computer code. Using Python, a language designed for teaching and learning how to program, you'll learn key skills that every coder needs. First, your instructor Ana Bell guides you through installing Python onto your computer. Then, you'll work through a few super-easy (and fun!) examples that teach you about how Python looks and works. After you get started, you'll learn how to build programs that can automatically repeat actions and make decisions based on the conditions YOU set. You'll get experience with the process of program writing, and learn to combine different pieces of code so that they can work together. Finishing everything off, you'll learn ways to make your code more readable and easier to maintain in the future. This video course works perfectly alongside Ana's book Get Programming: Learn to code with Python, each building on the other to give you a complete tour of this great language!"--Resource description page
Title from resource description page (Safari, viewed June 8, 2020)
Keywords: Python (Computer program language); Python (Langage de programmation); Electronic videos